The influence of human resource competency, utilization of information technology, and understanding of financial accounting standards on the quality of financial reports with an internal control system as an intervening variable at the GMAHK Head Office of the Eastern Indonesian Conference Union - Wahongan, Larey; Tinangon, Jantje J.; Wokas, Heince R. N. (Yayasan Widyantara Nawasena Raharja, 2024)
This study aims to examine the effect of human resource competency, utilization of information technology, and understanding of financial accounting standards on the quality of financial reports with an internal control system. This study uses primary data with 104 employees of the finance department at the Seventh-day Adventist Church (GMAHK) of the Eastern Indonesian Conference Union as respondents. This study uses path analysis for hypothesis testing. The findings show that human resource competence, understanding of accounting standards, and internal control systems have direct effect on quality of financial reports. In addition, the findings also show that human resource competence and a good understanding of accounting standards directly effect on the internal control system. In an indirect relationship, human resource competence and understanding of accounting standards are able to synergize with an effective internal control system in presenting quality financial reports. The findings of this study also indicate that information technology in GMAHK does not have a significant role in determining the quality of financial reports. The findings suggest that GMAHK needs to develop staff training, especially in mastering new information technology applications to ensure the continued quality of financial reports.